2019
DOI: 10.1111/nph.16266
|View full text |Cite
|
Sign up to set email alerts
|

Distinct fine‐root responses to precipitation changes in herbaceous and woody plants: a meta‐analysis

Abstract: Precipitation is one of the most important factors that determine productivity of terrestrial ecosystems. Precipitation across the globe is predicted to change more intensively under future climate change scenarios, but the resulting impact on plant roots remains unclear.Based on 154 observations from experiments in which precipitation was manipulated in the field and root biomass was measured, we investigated responses in fine-root biomass of herbaceous and woody plants to alterations in precipitation.We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 57 publications
4
53
0
Order By: Relevance
“…This adaptation mechanism of plants for the adverse environment is consistent with the reality [24]. The herbaceous plants were more vulnerable to drought stress than woody plants duo to their shallow root distribution and inaccessibility to deep water [25,26]. The results in this study display that the herbaceous plants in the cultivated soil have higher leaf IWHC, WTR and water contents, as compared to the woody plants in the moderate rocky desertification soil.…”
Section: Discussionsupporting
confidence: 86%
“…This adaptation mechanism of plants for the adverse environment is consistent with the reality [24]. The herbaceous plants were more vulnerable to drought stress than woody plants duo to their shallow root distribution and inaccessibility to deep water [25,26]. The results in this study display that the herbaceous plants in the cultivated soil have higher leaf IWHC, WTR and water contents, as compared to the woody plants in the moderate rocky desertification soil.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, responses of root biomass and R a to precipitation change were negatively asymmetrical. Drought has been found to inhibit root production and increase root mortality in grasslands (Wang et al., 2020; Wilcox et al., 2017), which not only directly suppressed R a , but also inhibited R h through the reduction in root exudates (Zhang, Li, et al, 2019). However, high precipitation could relieve water restriction and decrease C allocation to belowground in grasslands, leading to a nonsignificant response of root biomass (Figure 5d).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with herbaceous plants, trees have deeper rooting depth (Canadell et al., 1996), and soil water can be redistributed from wet deep layers to dry surface layers through their root system by hydraulic lift (Prieto, Armas, & Pugnaire, 2012). Therefore, R s in forests may be more buffered from drought than that in grasslands (Davidson, Nepstad, Ishida, & Brando, 2008; Wang, Huang, & Hu, 2020). In addition, fine‐textured soils with good water holding capacity in most forests could weaken the effect of water stress from precipitation reduction on microbial and root activities (Liu, Liu, et al, 2016; Shi, Cheng, Liu, & Jiang, 2005), leading to neutral (Brando et al., 2008; Davidson, Ishida, & Nepstad, 2004; Davidson et al., 2008) or even positive (Cleveland, Wieder, Reed, & Townsend, 2010; Liu, Liu, et al, 2016) responses of R s to drought.…”
Section: Introductionmentioning
confidence: 99%
“…This proposed plant adaptation mechanism under adverse environments is consistent with a previous study [ 31 ]. Herbaceous plants are more vulnerable to drought stress than woody plants, due to their shallow root distribution and inability to access deep water [ 32 , 33 ]. The results of this study showed that herbaceous plants grown in agricultural soil had higher leaf IWHC, WTR and water contents than the woody plants grown in moderately rocky desertified soil.…”
Section: Discussionmentioning
confidence: 99%